2016
DOI: 10.1002/mawe.201600604
|View full text |Cite
|
Sign up to set email alerts
|

Simulation based reduction of residual stress related part distortion

Abstract: During machining of structural components, material inherent stresses are removed and additional residual stresses are induced into the subsurface of the workpiece. Both effects may result in distortions of the workpiece leading to shape deviations and time consuming repair processes. The research objective of this paper is to reduce part distortion caused by residual stresses of machined aircraft components by utilizing a distortion simulation in advance. The presented method is able to predict the part disto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…Residual stresses introduced by machining have an impact in a superficial layer with a depth range of 250-300 µm [35,36], therefore, they must be included in the distortion simulation for parts with thin wall thickness t < 4 mm [37]. For this class of parts, the no inclusion of machining-RS can lead to a different pattern of distortion respect to the numerical prediction [38].…”
Section: Residual Stresses After Machiningmentioning
confidence: 99%
“…Residual stresses introduced by machining have an impact in a superficial layer with a depth range of 250-300 µm [35,36], therefore, they must be included in the distortion simulation for parts with thin wall thickness t < 4 mm [37]. For this class of parts, the no inclusion of machining-RS can lead to a different pattern of distortion respect to the numerical prediction [38].…”
Section: Residual Stresses After Machiningmentioning
confidence: 99%
“…To predict part distortions, models based on the finite element method have been proposed in the literature. 11–18 Finite element (FE) models aim to reduce part rework and scrap costs through the minimization of its distortions. In this sense, Dreier et al.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, Dreier et al. 12 showed that numerical simulations are effective to determine the optimized part position inside rolled plates in the presence of residual stresses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At a theoretical level, if the RS in a part are known in advance, a proper machining sequence could be planned with the aim to mitigate or counteract a warped geometry. This strategy is already implemented for parts machined from rolled plates, where RS can be considered as constant along the longitudinal direction [38]. However, for forgings, RS are a function of the geometry and, as a result, a complex three-dimensional stress field is present.…”
Section: 2mentioning
confidence: 99%